Pengaruh Asimetri Informasi, Ukuran Perusahaan, Leverage dan Profitabilitas pada Manajemen Laba - Yanti, Tia Rahma; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p26, 2019)
Earnings management arises as an effect of agency problems where there is an inconsistency in interests between owners and management. This study aims to determine whether information asymmetry, company size, leverage, and profitability influence earnings management. This research was conducted at Manufacturing Companies listed on the Indonesia Stock Exchange for the 2014-2016 period. The number of samples in this study were 33 manufacturing companies. This study uses a nonprobability sampling approach with a purposive sampling method. The analysis technique used is multiple linear regression analysis. Based on the results of the research analysis it can be seen that the information asymmetry variable has no effect on earnings management. Firm size measured by asset log has a significant negative effect on earnings management. While leverage and profitability have a positive and significant effect on earnings management. Keywords : Earnings management, information asymmetry, company size, leverage, and profitability.